Functional and Structural Outcomes of Temporal Zone II-Sparing Laser Photocoagulation Combined with Intravitreal Bevacizumab in Retinopathy of Prematurity - Eoi Jong Seo; Joo Yong Lee (Journal of Ophthalmology)
Background/Aim. The aim of the study was to investigate the outcomes of temporal Zone II-sparing laser photocoagulation combined with intravitreal bevacizumab (IVB) in patients with Type 1 retinopathy of prematurity (ROP) in Zone I. Methods. Medical records of 74 eyes of 37 infants were analysed. Only infants with Type 1 ROP in Zone I were included. Thirty-two eyes were treated with temporal-sparing laser + IVB. Both Zone I and temporal Zone II were spared to minimise potential visual field loss. Forty-two eyes were treated with laser alone conventionally. Early treatment outcomes, late complications, and refractive errors were analysed. Results. The mean gestational age and birth weight of the enrolled patients were 25.7 ± 2.5 weeks and 798.8 ± 440.2 g, respectively. In the combined treatment group, plus sign regression was achieved faster (12.1 ± 6.2 days vs. 25.6 ± 21.3 days, p=0.011) and retreatment was required less (0% vs. 23.8%, p=0.004) than in the laser-alone group. Retinal/preretinal haemorrhages occurred more often in the laser-alone group (42.9% vs. 9.4%, p=0.002). Normal development of temporal retinal vessels was also observed in twelve eyes in the combined treatment group. No differences in late complications or refractive errors were observed between the groups. Conclusion. Temporal Zone II-sparing laser treatment combined with IVB showed good early treatment outcome and temporal retinal vessels development.